POLITIK TRANSAKSIONAL DALAM PERSPEKTIF HUKUM ISLAM DI INDONESIA - L., Sudirman (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This article describes the problem of transactional politics in the Islamic legal perspective. The results of the assessment with the understanding that the approach to literature obtained political behavior that occurred at this time in order to try to influence a person or group of people behave or act in accordance with the wishes of the first, by any means. The ways that used to be inducement, coercion or incentives to construct a second party. Political bargaining may be the threat of punishment, it can also be lucrative offers. First party power base to influence the second variety, can be monetary, political office and control of negative information about the second. Political practice as it was away from the political ethics in Islam. In the Quran, Allah Swt. commands Muslims to choose good leaders and the faithful, and to do justice. Because if the leader is good, smart, healthy, honest and not corrupt, fair and trustworthy people will surely prosper and prosper.